799. A Pseudo-Outbreak of Pseudomonas fluorescens Infections. (4th December 2021) - Jaber, Tariq; Saini, Vikram; Morris, Laura; Como, James D; Bhanot, Nitin; Min, Zaw
Abstract: Background: Pseudomonas fluorescens is a water-borne pathogen that has been associated with outbreaks from transfusion of contaminated blood products or medical equipment. Our institution had a cluster of cultures that grew an uncommonly encountered microbe P. fluorescens within a period of one week. This prompted an internal investigation. We summarize the investigational process that led to the resolution of this pseudo-outbreak. Methods: We conducted a retrospective chart review of surgical and non-surgical patients with cultures positive for P. fluorescens from July 2 nd to July 8 th 2020. Baseline patient characteristics, clinical course, laboratory data, use of blood-associated products, and microbiology cultures were analyzed. Results: Eight patients were identified with positive tissue cultures for P. fluorescens . Among those, 5 specimens (62.5%) were from osteoarticular sites (1 prosthetic hip, 1 prosthetic knee, 1 right foot, 1 sternum, and 1 vertebral source). One culture (12.5%) was obtained from a sacral soft tissue wound. Two tissue specimens (25%) were collected from respiratory sites (1 lung tissue and 1 bronchoalveolar lavage). No association with specific surgical personnel or operating room was identified. During routine specimen processing, a small amount of sterile normal saline is added to the conical grinder prior to culture preparation. It was discovered that a non-sterile normal saline had been inadvertently utilized during that step. These eight tissue specimens were subsequently reprocessed with sterile solution; P. fluorescens was not re-isolated. Specimen processing protocols were reinforced. Adjustment of antimicrobial therapy was made accordingly without reported subsequent adverse clinical outcomes. Conclusion: A multi-faceted team approach in collaboration with Infection Prevention, Infectious Diseases, Surgery, operating room personnel, and Microbiology identified an unintended breakdown in sterile laboratory protocols which resulted in a cluster of falsely positive cultures. An increased incidence of infection with an uncommon pathogen initiated a prompt investigation that resulted in the identification of a pseudo-outbreak event. Disclosures: All Authors : No reported disclosures